CD4+ skin resident memory T cells preferentially colocalize with dermal Folr2hi macrophages in contact hypersensitivity - Murata, Akihiko; Tokoyoda, Koji (Frontiers in Immunology, 2025)
In contact hypersensitivity (CHS), local immune memory is established in previously affected skin through the formation of CD4+ and CD8+ tissue-resident memory T (TRM) cells. This memory contributes to disease recurrence by enhancing local antigen responsiveness and is maintained in the long term by TRM cells, particularly CD4+ TRM cells. However, the mechanisms underlying the maintenance and reactivation of CD4+ TRM cells remain unclear. We herein examined the cellular niches persistently interacting with CD4+ T cells in naïve and CHS-healed mouse ear skin. Most CD4+ T cells were scattered in the dermis and colocalized with Folr2hi macrophages, a previously unrecognized skin macrophage population, suggesting a physical interaction. In contrast, fewer than 20% of CD4+ T cells colocalized with dendritic cells (DCs) or other cell lineages. The administration of an anti-colony stimulating factor 1 receptor (CSF1R) antibody depleted nearly all Folr2hi macrophages and several other myeloid cells, while the maintenance and reactivation of CD4+ T cells as well as other αβ T cells in healed skin remained unaffected. Moreover, in macrophage-depleted healed skin, CD4+ T cells did not establish new interactions with remaining antigen-presenting cells, and their contact rate with DCs remained unchanged. These results indicate that local immune memory in CHS-experienced skin is maintained and functions independently of CSF1R-dependent myeloid cells, including Folr2hi macrophages, despite their predominant colocalization with skin CD4+ TRM cells.